Is information something ontological, or physical or perhaps something else? Some remarks on R. Krzanowski approach to concept of information - Mścisławski, Łukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
As one may have noticed, the title of this paper is somewhat provocative. We found Roman Krzanowski’s (2020a,b,c; 2022) proposed approach to the problem of information very intriguing. Our aim here is to highlight some advantages when it comes to answering some fundamental questions in the philosophy of physics and metaphysics, as well as the philosophy of information and computer science. This issue is of great importance, so we propose that the introduction of some subtle distinctions between ontological and epistemological information can be regarded as being analogous to G.F.R. Ellis’s analyses of the passage of time in his concept of the Crystallizing Block Universe (Ellis and Goswami, 2012). This analogy could be useful when further studying the relations between different types of information. We also suggest some subjects for further study, ones where Krzanowski’s proposal could serve as a very solid foundation for examining traditional metaphysical issues by combining classical philosophical doctrines with the new approach.